Le coton dans tous ses états Textes du colloque du 12 mai 2006, Gembloux, Belgique - Berti, F.; Hofs, J. - L.; Mergeai, G. (Uliège Library, 2006)
In a globalized world economy, the production and sale of cotton is a major issue for the future of a significant portion of humanity. This is particularly true in sub-Saharan Africa, where it is estimated that more than 20 million people derive the bulk of their income from cotton. Thanks to immense efforts by the private sector, the public sector and cooperation agencies, what has been called "white gold" has become the backbone of the economies of many African countries over the past thirty years. Its dissemination has been accompanied by a significant increase in the performance of production systems in savannah areas and, following the redistribution of income that it has allowed in the rural world, a notable improvement in the living conditions of the populations concerned. This undeniable success in the fight against poverty in sub-Saharan Africa is now threatened by the downward trend in world cotton fiber prices, largely caused by the subsidies granted to cotton producers in the North and by the increase in production and transportation costs, mainly linked to the continuing rise in energy prices. The search for fair, efficient and sustainable solutions to the deep crisis currently facing the African cotton industry is an issue to which our institution is particularly sensitive. Not only because of our natural interest in everything related to rural development in Africa, but also because of the long history that links Gembloux to cotton growing and the expertise acquired over the last few years by the Economics and Rural Development Unit of our institution in analyzing the functioning of the African cotton sectors. Professor Demol, who during his long and brilliant career was one of the main actors of the international recognition we have acquired in cotton research, will briefly introduce the afternoon session by talking about the almost one hundred years of history linking our Faculty to cotton in Africa. The theme chosen by the Board of Directors of our institution for this academic year 2005-2006 being "cooperation and development", it is quite natural that the theme of the African cotton crisis has been chosen for the study day which is traditionally organized within the framework of the theme year. We thought it wise to benefit from his insight as a field actor as well as from that provided by the internationally renowned specialists we invited to participate in this day to better understand the issues and challenges facing cotton growing in Africa and to identify possible solutions to overcome the crisis.